Incidencia de la atención al cliente interno y externo en la imagen del institutode posgrado de la Universidad Nacional de Chimborazo período octubre 2014- abril 2015. - Sinche León, Ángel José (2016)
The investigation: INCIDENCE OF ATTENTION TO INTERNAL AND EXTERNAL CLIENT IN IMAGE OF POSTGRADE INSTITUTE AT NATIONAL UNIVERSITY OF CHIMBORAZO DURING THE PERIOD OCTOBER 2014 – APRIL 2015.To give solution to the formulated problem: How does affect the attention to internal and external client in the administrative area of the Postgrad Institute during October - April, 2015? And with the target to determine how affects image, attention to the internal and external client in administrative area Post grade Institute during period October 2014 - April, 2015. The realized investigation answered to relevancy study in the Postgrad Institute that needs space and strategy for give attention to the demand of a large number of internal and external users who come every day for private and public defenses. The theoretical contribution of research work establishes: the management organization model of the Postgrad Institute with practice, it will determine the requests and will establish client attention strategies. The direct beneficiaries are the personnel that works of the Post grade Institute: The Director, Secretary, Coordinators and the indirect beneficiaries will be the students who need ideal and opportune attention. This investigation is based in: Attention to the client, communication and institutional image. The hypothesis applied is: The attention to client affects positively the institutional image of the Postgrad Institute, The variables are: Independent: Attention to the client, and Dependent: Institutional image. The method used was the deductive hypothetical method, with a Descriptive Investigation. In the present investigation 355 surveys were applied with, affirmative and negative questions. After analyzed and tabulated the surveys, a value of Chi-Square (82.56) is obtained, the same establishes that: The attention to client affects positively the institutional image the Post grade Institute. An Attention Model to Client is proposed, to establish attention strategies with the General Target to contribute with management and organization model of the Postgrad Institute, to establish attention to client through administrative strategies, coming to the conclusion: that attention to internal and external client affects the administrative image the Post grade Area.